Further Validating the Robotic Microsurgery Platform through Preclinical Studies on Rat Femoral Artery and Vein - Cho, Jeongmok; Kim, Donggeon; Kim, Taehyun; Pak, Changsik John; Suh, Hyunsuk Peter; Hong, Joon Pio (Journal of Reconstructive Microsurgery, 2025)
This research aims to validate the proficiency and accuracy of the robotic microsurgery platform using rat femoral vessel model.A total of 256 rat femoral vessels were performed, half using robotic and the other by manual microanastomosis by eight microsurgeons with less than 5 years of experience given eight trials (rats) each. Vessel demographics, proficiency (duration of suture and Structured Assessment of Robotic Microsurgical Skills [SARMS]), and accuracy (patency and scanning electron microscopic [SEM]) were analyzed between the two groups.Using the robot, an average of four trials was needed to reach a plateau in total anastomosis time and patency. Significant more time was required for each vessel anastomosis (34.33 vs. 21.63 minutes on the eighth trial, p < 0.001) one factor being a higher number of sutures compared with the handsewn group (artery: 7.86 ± 0.51 vs. 5.86 ± 0.67, p = 0.035, vein: 12.63 ± 0.49 vs. 9.57 ± 0.99, p = 0.055). The SARMS scores became nonsignificant between the two groups on the fourth trial. The SEM showed a higher tendency of unevenly spaced sutures, infolding, and tears in the vessel wall for the handsewn group.Using the robot, similar patency, accuracy, and proficiency can be reached through a fast but steep learning process within four trials (anastomosis of eight vessels) as the handsewn group. The robotic anastomosis may take longer time, but this is due to the increased number of sutures reflecting higher precision and accuracy. Further insight of precision and accuracy was found through the SEM demonstrating the possibility of the robot to prevent unexpected and unwanted complications.
Keywords: robotic microsurgery; supermicrosurgery; robotic-assisted surgery